Numerical modeling of rebar buckling in reinforced concrete members using truss analogy - Sadık Can Girgin (Pamukkale University Journal of Engineering Sciences, 2018)
Reinforced concrete (RC) structures in earthquake prone regions are designed to achieve the seismic performance objectives. In end regions of RC members, longitudinal reinforcing bars may develop buckling due to high compressive strains under reversed cyclic loadings. The performance based assessment for RC structures should rely on analytical models which can account for the effect of rebar buckling on the nonlinear response. This study extends a previously proposed nonlinear truss modeling approach for modeling RC elements whose response is affected by rebar buckling. Nonlinear truss model includes diagonal truss elements accounting for biaxial effects in compression and tension stiffening for concrete elements in the horizontal and vertical directions. The truss elements representing reinforcing steel are provided with a uniaxial material model which can explicitly account for inelastic buckling and fracture of rebars. The modeling approach is validated with experimental test results on one RC beam considering mesh size effects on the response. Numerical model computed strength degradation in moment-drift ratio response of the beam in accordance with the experimental results.